La naturaleza como facilitadora del aprendizaje de una lengua adicional - Tavella, Gabriela; Férnandez, S. Carina; Porto, Melina (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
This classroom account presents a didactic sequence located outdoors, in which nature enhanced the learning of an additional language. Likewise, aspects of intercultural education were addressed through CLIL pedagogy. The sequence was complemented with a translanguage approach, which allowed all languages to coexist synergistically and all students to express meanings through any of the available languages or to use any other mode of communication. Both teachers and students were able to transcend the instrumental purpose of language learning and consider its educational purpose.